2023
DOI: 10.3390/v15020528
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Control Intervention Scenarios for Raccoon Rabies in Southern Ontario between 2015 and 2025

Abstract: The largest outbreak of raccoon rabies in Canada was first reported in Hamilton, Ontario, in 2015 following a probable translocation event from the United States. We used a spatially-explicit agent-based model to evaluate the effectiveness of provincial control programs in an urban-centric outbreak if control interventions were used until 2025, 2020, or never used. Calibration tests suggested that a seroprevalence of protective rabies antibodies 2.1 times higher than that inferred from seroprevalence in progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Despite the relatively low RVNA response in this study when compared to rural ONRAB studies, case reduction and apparent elimination during the study was observed. This phenomenon of low RVNA response with case reduction has also been observed in urban Hamilton, Ontario, Canada, where seroprevalence was only 6–14% (Acheson et al 2023), yet RRV cases declined from 256 in 2016 to 23 in 2022 (Ontario Ministry of Natural Resources and Forestry 2023). Despite 5 yr of no cases in our study area, 19 cases of RRV were reported in 2022 (174 negatives, 10% positive) and five cases between January and March 2023.…”
Section: Discussionmentioning
confidence: 63%
“…Despite the relatively low RVNA response in this study when compared to rural ONRAB studies, case reduction and apparent elimination during the study was observed. This phenomenon of low RVNA response with case reduction has also been observed in urban Hamilton, Ontario, Canada, where seroprevalence was only 6–14% (Acheson et al 2023), yet RRV cases declined from 256 in 2016 to 23 in 2022 (Ontario Ministry of Natural Resources and Forestry 2023). Despite 5 yr of no cases in our study area, 19 cases of RRV were reported in 2022 (174 negatives, 10% positive) and five cases between January and March 2023.…”
Section: Discussionmentioning
confidence: 63%
“…However, operational efforts in Hamilton suggest it is possible to contain and even eliminate RRV with seroprevalence lower than 60%. Indeed, ongoing simulation analyses indicate that RRV elimination in Hamilton may be possible at a seroprevalence threshold closer to 30–40% (Acheson et al 2023). If a threshold of 40% would be sufficient for RRV control and elimination, a combination of lower-effort TVR and helicopter baiting at a typical target density could achieve adequate seroprevalence in raccoons while representing nearly half the cost of a TVR-only strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, it may be safer to compare relative seroprevalence instead of absolute seroprevalence. Studies have also demonstrated a cumulative impact of baiting annually across years for reaching seroprevalence targets and case elimination (Davis et al 2019; Acheson et al 2023), whereas a single-season population simulation without disease may yield more limited predictions in the context of long-term RRV control programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding upon previous studies of RABV circulation in North American bats, the most important factor that influences the virus’ spread between Myotis bat species is range overlap, in contrast to the important role of host genetic diversity in constraining transmission between different bat genera [ 10 ]. Another study explores the use of a spatially explicit agent-based computer model, which incorporates aspects of host and pathogen biology and different control scenarios to simulate spatio-temporal rabies dynamics across Southern Ontario following the introduction of raccoon rabies [ 11 ]. Although such models can predict disease outcomes under many different scenarios, thereby informing rabies wildlife control programs, accounting for all factors that impact disease transmission in this field is still challenging.…”
mentioning
confidence: 99%